The expression of neurological soft signs in two African populations with first-episode schizophrenia (2018)
Information about patterns of expression of neurological soft signs (NSS) in schizophrenia among individuals belonging to the same genetic ancestry may provide new insight for the understanding of the disease’s genetic functions. This study aimed to investigate whether patterns of NSS expression in first episode schizophrenia are com parable in populations with dissimilar genetic ancestry. A sample of 207 patients with first episode schizophrenia were examined using the Neurological Evaluation Scale before they were exposed to anti-psychotics. They were allocated to two African ancestry groups: Black (81 Yoruba Nigerians, and 18 Xhosa South Africans), and non-Black (98 Colored, and 10 White South Africans). Assessments were carried out using validated measures of clinical characteristics of schizophrenia. We determined the frequency, severity, factor structure, and association of NSS with clinical characteristics. Factor derived categories were compared using the Pearson’s (r) and Tucker’s congruence methods. The associations between factor derived categories and clinical characteristics of schizophrenia were determined using Pearson’s correlations and multiple regression analyses. Neurological soft signs were more frequent and more severe in the Black African ancestry group. Also, the factor structure and presentation of NSS in the two ancestry groups were significantly different. Neurological soft signs, especially motor sequencing and cognitive-perceptual abnormalities, were independently associated with disorganization psychopathologies in all the participant groups. Differences in the profile of NSS in Black compared with non-Black African ancestry patients with first episode schizophrenia may suggest differing patterns of expression of NSS in schizophrenia according to genetic ancestry.